Biofilm activity and sludge characteristics affected by exogenous N-acyl homoserine lactones in biofilm reactors. (July 2016) - Hu, Huizhi; He, Junguo; Liu, Jian; Yu, Huarong; Zhang, Jie
Graphical abstract: Highlights: AHL concentration has clear effect on mature biofilm. Introduction a parallel-system concentration of AHLs could enhance biofilm activity. The removal of COD and nitrogen could be improved by dosing an appropriate AHLs content. Adding higher concentration of AHLs can destroy the balance between QS and QQ. Abstract: This study verified the effect of N-acyl homoserine lactone (AHL) concentrations on mature biofilm systems. Three concentrations of an AHL mixture were used in the batch test. Introducing of 5 nM AHLs significantly increased biofilm activity and increased sludge characteristics, which resulted in better pollutant removal performance, whereas exogenous 50 nM and 500 nM AHLs limited pollutant removal, especially COD and nitrogen removal. To further identify how exogenous signal molecular affects biofilm system nitrogen removal, analyzing of nitrifying bacteria through real-time polymerase chain reaction (RT-PCR) revealed that these additional signal molecules affect nitrifying to total bacteria ratio. In addition, the running state of the system was stable during 15 days of operation without an AHL dose, which suggests that the changes in the system due to AHL are irreversible.